Les processus de socialisation chez les enfants de l'école primaire au prisme d'un réaménagement de l'espace de jeu par les adultes - Sophie Levrard
The school is subject to special attention in terms of its architecture which is intended to be innovative. In the sociology of childhood, it is more the effects of the development of the school space on children and in particular on their processes of socialization that interest us. We hypothesized that changing school play spaces challenges the social organization of children. To demonstrate it, we have been investigating a rural school with children aged 6 to 11. Two situations of play directly and indirectly induced by adults are the subject of an in-depth study to identify elements of understanding on processes of socialization between children. We have shown that children, as actors, are appropriating the spaces to create territories in which the social group sets up stable standards and variable socialisation processes according to the intervention more or less direct adults and space available.